A Novel Framework Design for Test Case Authoring and Auto Test Scripts Generation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Every product has defects and identifying defects in the process of development and rectifying them before the launch of the product is very important. Embedded software testing process find the bugs in the software and report to the developer to fix issues. Sometimes to meet the product release deadlines, test engineers will not get much time to cover all test cases. That is why most software testing depends on test automation. In this paper, we focused on the area of automotive and home appliances embedded software test automation. Test automation is the only solution to improve the test phase and meet the timeline of the product launch. There are many test Automation tools like LabVIEW, test stand, and automation desk to automate testing embedded software. However, there is still manual efforts are required to use these tools. This paper deals automate those manual efforts. This Works shows how to generate test scripts from test cases to reduce the manual efforts, time, and cost.